2007
DOI: 10.1242/jeb.009498
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and energetic factors underlying gait transitions in bluegill sunfish (Lepomis macrochirus)

Abstract: transition point. The cost of transport, measured by respirometry, increased as the fish switched from labriform to undulatory swimming. Our data show that bluegill changed gait as swimming speed increased to recruit additional muscle mass, rather than to maximize economy, as is the case for many terrestrial animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
54
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 40 publications
5
54
0
1
Order By: Relevance
“…Pectoral fin-beat frequency is positively related to swimming speed and/or oxygen consumption in several species of labriform fishes (e.g. Mussi et al, 2002;Kendall et al, 2007;Tudorache et al, 2009;Johansen et al, 2010). Some authors have suggested that the relationships between fin-beat frequency, oxygen consumption rate and swimming speed in a given fish species may provide useful indicators of swimming energetics in the wild, which are extremely difficult to estimate in aquatic species (Steinhausen et al, 2005;Ohlberger et al, 2007;Tudorache et al, 2009;Layton, 2011).…”
Section: Research Articlementioning
confidence: 99%
“…Pectoral fin-beat frequency is positively related to swimming speed and/or oxygen consumption in several species of labriform fishes (e.g. Mussi et al, 2002;Kendall et al, 2007;Tudorache et al, 2009;Johansen et al, 2010). Some authors have suggested that the relationships between fin-beat frequency, oxygen consumption rate and swimming speed in a given fish species may provide useful indicators of swimming energetics in the wild, which are extremely difficult to estimate in aquatic species (Steinhausen et al, 2005;Ohlberger et al, 2007;Tudorache et al, 2009;Layton, 2011).…”
Section: Research Articlementioning
confidence: 99%
“…This species swims in the labriform mode at low speeds, generating lift and thrust by beating the pectoral fins (Gibb et al, 1994;Drucker and Lauder, 1999;Drucker and Lauder, 2000). As swimming speed increases, bluegill change gait from labriform swimming to combined use of their pectoral fins and undulations of the body axis (Gibb et al, 1994;Jones et al, 2007;Kendall et al, 2007). Gait changes may maximize locomotor economy and/or be driven by mechanical factors such as the limits to muscle power or the need to minimize mechanical stresses (Alexander, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Gait changes may maximize locomotor economy and/or be driven by mechanical factors such as the limits to muscle power or the need to minimize mechanical stresses (Alexander, 1989). When swimming at their acclimation temperature (T a ), the labriform-undulatory gait change in bluegill is primarily driven by the need to recruit additional muscle mass to meet the power requirements of higher speed swimming (Kendall et al, 2007). In ectotherms, environmental temperature is an additional factor determining gait transition speed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations